Opportunities and Threats of Online Loans During the Covid-19 Outbreak: The Importance of Disseminating Sharia Economic Law to South Kalimantan Society - Firqah Annajiyah Mansyuroh; Rahmat Fadillah (Proceeding International Seminar of Islamic Studies, 2022)
During the covid-19 outbreak, there was a drastic decrease in income with living expenses that still had to be met, causing people to finally decide to take out loans to meet their daily needs. This also happened to the people of South Kalimantan, where there were cases of illegal online loans that violated sharia economic law in various aspects. This paper examines the importance of disseminating sharia economic law during the covid-19outbreak.This topic is theoretically and practically important in legal culture. Public Understanding of the opportunities and threats of online loans cannot be separated from the intensity of dissemination and counseling carried out to society.This research combinesempirical legal analysis with survey method to see how the opportunities and threats of online loans are according to South Kalimantan's people. The results of this study will show that public welfare and the principle of legal fiction must be supported by the dissemination of law to the entire public of South Kalimantan.Keywords: Online Loan; Disseminating Sharia; Economic Law